Hubungan Pengetahuan tentang Covid-19 dengan Tingkat Kepatuhan Anak Remaja Menjalankan Protokol Kesehatan di Indonesia - Hikmah, Insiyatul; Rosyidah, Hanifatur; Adyani, Kartika (Jurnal Kesehatan, 2021)
The lack of knowledge about Covid-19 that teenagers have will cause teenagers to not comply with health protocols in Indonesia so that the spread of Covid-19 becomes uncontrollable. The purpose of this study is to determine the relationship between knowledge about Covid-19 and the level of compliance of adolescents in carrying out health protocols in Indonesia. The research design method was quantitative with a cross-sectional approach. The research subjects were adolescents in Indonesia with 400 respondents conducted on 29 October - 11 November 2020. The sampling technique used was snowball sampling with research instruments using a questionnaire with the chi-square test. There is a relationship between adolescent knowledge about covid-19 and handwashing (p-value=0,000), there is a relationship between adolescent knowledge about Covid-19 using masks (p-value=0,000) and there is between adolescent knowledge about Covid-19 and social distancing (p-value=0,006). It is hoped that the results of this study can be used as information material regarding the relationship between knowledge about Covid-19 and the level of compliance of adolescents in carrying out health protocols in Indonesia, for adolescents, it is hoped that they can increase knowledge about Covid-19 by watching the news on TV, reading newspapers, social media and from health workers, for further researchers, it is hoped that they need to conduct research with qualitative methods and use more varied variables related to knowledge about Covid-19 with the level of compliance of adolescents in carrying out health protocols in Indonesia.